Innate lymphoid cells, possible interaction with microbiota - Moro, Kazuyo (Semin Immunopathol, 2014)
Recent studies have identified novel lymphocyte subsets named innate lymphoid cells (ILCs) lacking antigen-specific receptors. ILCs are present in a wide variety of epithelial compartments and occupy an intermediate position between acquired immune cells and myeloid cells. ILCs are now classified into three groups: group 1 ILC, group 2 ILC, and group 3 ILC based on their cytokine production patterns that correspond to the helper T cell subsets Th1, Th2, and Th17, respectively. ILCs play important roles in protection against various invading microbes including multicellular parasites, and in the maintenance of homeostasis and repair of epithelial layers. Excessive activation of ILCs, however, leads to various inflammatory disease conditions. ILCs have thus attracted interests of many researchers in the fields of infectious immunity, inflammatory diseases, and allergic diseases. Because epithelial cells sense alterations in environmental cues, it is important to understand the functional interaction between epithelial cells, ILCs, and environmental factors such as commensal microbiota. We discuss in this review developmental pathways of ILCs, their functions, and contribution of commensal microbiota to the differentiation and function of ILCs.